Evaluation of the Conformity of the Budget Realization Report (LRA) with PSAP No.02 at the Lhokseumawe City PUPR Office - Nurmasyitah; Iskandar Iskandar; Muammar Khaddafi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The Budget Realization Report (LRA) is one of the main components in the local government's financial statements which functions as a means to assess the performance of budget implementation in a transparent and accountable manner. PSAP Number 02 stipulates that the LRA must be prepared using a cash basis and contain components such as revenue, expenditure, transfers, surplus/deficit, financing, and the Remaining Over/Under-Financing Budget (SiLPA/SikPA). This study aims to evaluate the suitability of the presentation of LRA at the Public Works and Spatial Planning Office (PUPR) of Lhokseumawe City against the provisions of PSAP 02 for the 2021 to 2023 fiscal years, as well as identify obstacles in its implementation. The method used in this study is a qualitative descriptive approach with document study techniques and literature analysis. Data is obtained through official LRA documents available online, audit reports of the Financial Audit Board, as well as academic and policy references related to government accounting standards. The results of the study show that the preparation of LRA by the PUPR Office has followed the structure and format as stipulated in PSAP 02. The report presents separate and complete budget and realization data, and includes all mandatory components. The implementation of the cash base has also been generally well implemented, although there is a delay in recognizing transactions at the end of the budget period. The main obstacles found include limited human resources who have a technical understanding of PSAP, accounting information systems that have not been fully integrated, and insynchronization between central policies and their implementation in the regions. Therefore, it is necessary to strengthen the competence of the apparatus, increase the capacity of the information system, and adjust technical regulations to ensure that regional financial reporting runs according to the set standards.